Hemodynamic study in humans in hot climates (Experimental biology, 2015)
Hemodynamic parameters were studied in people living in hot climates Kazakhstan. It is shown that the process of adaptation to the hot climate manifest compensatory reactions of two types. The first stage of the reaction is expressed compensatory slowing of heart rate , blood pressure decrease and peripheral resistance to blood flow . Deminutionsimultaneous elongation of isometric contraction phase and exit phase shortening testify economy myocardial energy expenditure . The second stage of compensatory physiological response of the cardiovascular system is characterized by some diastolic blood pressure increase so as peripheral resistance and promotes the body better blood flow .
Keywords: cardiohemodynamics; minimum; maximum blood pressure; venous pressure; blood flow velocity; systolic volume; seasonal changes; hot climate.